Considerations for Digital PCR as an Accurate Molecular Diagnostic Tool. (6th January 2020) - Huggett, Jim F; Cowen, Simon; Foy, Carole A
Abstract: BACKGROUND: Digital PCR (dPCR) is an increasingly popular manifestation of PCR that offers a number of unique advantages when applied to preclinical research, particularly when used to detect rare mutations and in the precise quantification of nucleic acids. As is common with many new research methods, the application of dPCR to potential clinical scenarios is also being increasingly described. CONTENT: This review addresses some of the factors that need to be considered in the application of dPCR. Compared to real-time quantitative PCR (qPCR), dPCR clearly has the potential to offer more sensitive and considerably more reproducible clinical methods that could lend themselves to diagnostic, prognostic, and predictive tests. But for this to be realized the technology will need to be further developed to reduce cost and simplify application. Concomitantly the preclinical research will need be reported with a comprehensive understanding of the associated errors. dPCR benefits from a far more predictable variance than qPCR but is as susceptible to upstream errors associated with factors like sampling and extraction. dPCR can also suffer systematic bias, particularly leading to underestimation, and internal positive controls are likely to be as important for dPCR as they are for qPCR, especially when reporting the absence of a sequence. SUMMARY: In this review we highlight some of the considerations that may be needed when applying dPCR and discuss sources of error. The factors discussed here aim to assist in the translation of dPCR to diagnostic, predictive, or prognostic applications.